Developing a vaccine distribution network between county towns - Seprényi, Kitti; Veres, Péter; Cservenák, Ákos (Advanced Logistic Systems - Theory and Practice, 2023)
Without the cold-chain network, it would be impossible in today's world to transport large quantities of perishable goods, primarily food and medicine, over long distances, but it is still very important that the necessary materials reach their destination on time and with adequate cooling. This is absolutely true for the vaccines created to stop the Covid-19 pandemic, which had to be distributed quickly and at certain storage temperatures to all parts of the world. This is a rather difficult task with NP-hard complexity. In this research, we are investigating the optimal way to get from a distribution center in Budapest to the county towns with transport vehicles, so that neither the vaccines deteriorate, nor we violate regulations. For this, we used vehicle route planning principles and Excel-Solver software.